Nominal Income Targeting : A Critical Evaluation - Argy, Victor (IMF Working Papers; Working Paper ;, 1991)
This paper evaluates the proposal that government authorities ought to target nominal income. It begins by viewing the literature in some detail. It then undertakes a theoretical analysis of the proposal first for the small country and next for the large country. There is then a general discussion of various issues posed by nominal income targeting. Finally, the paper summarizes the empirical work to date. We show that traditional theoretical analysis tends to be too simple and overly biased in favor of nominal income targeting. When more realistic assumptions are made or econometric simulations are undertaken the case for nominal income targeting is substantially weakened but not, however, destroyed.